Whoopi Goldberg presents Moms Mabley [videorecording (DVD)] : the original queen of comedy - Mabley, Moms; Goldberg, Whoopi, 1955-; Belafonte, Harry, 1927-; Cosby, Bill, 1937-; Griffin, Kathy, 1960-; Murphy, Eddie, 1961-; Rivers, Joan (Home Box Office ; Distributed by Warner Home Video, 2014)
An homage to "the funniest woman in the world", Jackie "Moms" Mabley, who emerged from African-American vaudeville to become a showbiz pioneer. Mabley, who broke racial and gender boundaries over the course of five decades, continues to inspire comedians today.